2018
DOI: 10.1007/s13593-018-0528-0
|View full text |Cite
|
Sign up to set email alerts
|

Designing a future food vision for the Nordics through a participatory modeling approach

Abstract: The development of future food systems will depend on normative decisions taken at different levels by policymakers and stakeholders. Scenario modeling is an adequate tool for assessing the implications of such decisions, but for an enlightened debate, it is important to make explicit and transparent how such value-based decisions affect modeling results. In a participatory approach working with five NGOs, we developed a future food vision for the Nordic countries (Denmark, Finland, Norway and Sweden) through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 28 publications
(38 reference statements)
1
15
0
Order By: Relevance
“…The Farm to Fork Strategy indicates similar notions in its ambition to include citizens and stakeholders, at several governance levels, when defining sustainable food and formulating policies. Previous research in the Nordic countries has shown that while there is agreement at large on the key challenges of food systems, local, regional, national, and supranational perspectives on strategies, mechanisms and priorities differ (Karlsson et al 2018). The results of this study point towards a similar conclusion, indicating the importance of governance and policies to be diverse, acting at multiple levels, and to be adaptive to accommodate several different possible transformation pathways (de Krom and Muilwijk 2019; Stringer et al 2020).…”
Section: Diversity Of Pathways For Food System Transformationssupporting
confidence: 73%
“…The Farm to Fork Strategy indicates similar notions in its ambition to include citizens and stakeholders, at several governance levels, when defining sustainable food and formulating policies. Previous research in the Nordic countries has shown that while there is agreement at large on the key challenges of food systems, local, regional, national, and supranational perspectives on strategies, mechanisms and priorities differ (Karlsson et al 2018). The results of this study point towards a similar conclusion, indicating the importance of governance and policies to be diverse, acting at multiple levels, and to be adaptive to accommodate several different possible transformation pathways (de Krom and Muilwijk 2019; Stringer et al 2020).…”
Section: Diversity Of Pathways For Food System Transformationssupporting
confidence: 73%
“…The involvement of the stakeholders in this study proved useful, and there was agreement between the authors and stakeholders on the knowledge gaps and future research needs, as well as some of the most important sustainability interventions. There were also some similarities between key interventions identified by stakeholders in this, and another recent study, aimed at developing a future food vision for the Nordic countries [22]. For example, the focus on small-scale farming, biogas production, and subsequent nutrient recycling, decreasing food wastage, and only using animals that can be fed using biproducts and waste streams (i.e., limited livestock production) was identified by stakeholders in both studies, while only one of the stakeholders interviewed for our study brought up the importance of organic farming, which was considered important in the Nordic study.…”
Section: Discussionmentioning
confidence: 57%
“…There are examples of studies that have examined sustainable food production in terms of environmental impacts as well as economic and social dimensions [9,22]. However, these rarely consider the entire food production chain or all relevant dimensions or focus on ReDiReL.…”
Section: Introductionmentioning
confidence: 99%
“…To understand how requiring the model to include some ASF in OMN diets would affect the environmental impacts, we optimized an OMN diet (OMN.1) with limits on ±80% of the current mean intake (g/day) of ASF-meats, dairy, eggs, fish/seafood, animal-fats. Several previous diet models indicate large reductions (≥80%) in ASF are required for minimized environmental impact 23,62 . Finally, to understand how NFFs may or may not be privileged over ASF in the model, we ran a last sensitivity analysis which allowed both ASF and NFF (OMN-NFF), subject to the original nutrition constraints and feasible consumption constraints on the intake of all food items.…”
Section: Sensitivity Analysesmentioning
confidence: 99%